Excellent permittivity-temperature stability and reliability performance of ultra-thin Ba0.97Ca0.03TiO3-based MLCCs. Issue 1 (2nd January 2023) - Huang, Xiong; Zhang, Lei; Wang, Pengfei; Jian, Gang; Yang, Jun; Li, Bo; Yu, Shuhui; Sun, Rong; Fu, Zhenxiao; Cao, Xiuhua
ABSTRACT: High-temperature stability and reliability are in high demand for ultra-thin multilayer ceramic capacitors (MLCCs), which are ubiquitous in electronic industries. Here, two doping matrices of BaTiO3 (BT) and Ba0.97 Ca0.03 TiO3 (BCT) are chosen to prepare ultra-thin MLCCs, whose effects on the microstructure, nonlinear dielectric properties, temperature stability, and reliability of the capacitors were investigated. Compared with BT-based MLCCs, BCT-based MLCCs possess better core-shell structures, thus, leading to a higher Schottky barrier for inhibiting carrier migration and improving aging performance. For the 1.5 μm-thickness capacitors using the BCT doping matrix rather than BT, the temperature coefficient of capacitance reaches the X7R standard, and the breakdown field increases from 148 to 172 V/μm. Moreover, the ability to resist insulation resistance degradation has been significantly improved. This work demonstrates the great potential of using BCT as the doping matrix to prepare ultra-thin MLCCs with excellent temperature stability and reliability.